SERBIAN AND BUNJEVAC CHARITIES IN THE SUBOTICA (Heritage, 2020)
The significance of this work for contemporary feminist theory is that it points to the fact that, although in recent years, the work of women's organizations and affiliates of the Serbian Charity Cooperative Society and the Circle of Serbian Sisters of Subotica has remained unlit.These are female politicians and humanitarians who, through their work through women's organizations, have worked to educate girls. They are Danica J. Konjovic, Mica Radic, Anastasia Manojlovic, Manda Sudarevic and others. The work was based on the material of the Historical Archives of the City of Subotica, the archives of the Serbian Orthodox Church Municipality in Subotica, as well as other relevant literature that dealt with the study of the importance of charities in Subotica. The paper deals with Bunjevke and Serb women from Subotica, because the general and scientific public know little about their work.
Keywords: feminism, women's movement,Dobrotvorna zadruga Srpkinja, Kolo srpskih Sestara, Others, Bunjevke